Lipid composition changes induced by tamoxifen in a bacterial model system - Luxo, Cristina (1998)
A putative relationship between growth impairment of Bacillus stearothermophilus by tamoxifen (TAM) and TAM-induced perturbation of the physical properties of bacterial membrane lipids has been observed. The supplementation of the growth medium with Ca2+ (a membrane stabilizer) partially relieves growth inhibition by TAM, allowing growth at TAM concentrations that fully impair growth in the basal medium. B. stearothermophilus modifies the membrane lipid composition in response to the addition of TAM to the growth medium and the response is sensitive to Ca2+. Changes in lipid composition are observed in the acyl chains and in the polar head groups of phospholipids. The physical effects of alteration in these lipids was studied by fluorescence polarization of DPH and DPH-PA. Polar lipid dispersions from TAM-adapted cells grown in a Ca2+ medium show a shift of Tm to higher temperatures and a significant increase of the structural order as compared to lipids from control cells, suggesting that TAM-induced lipid composition changes compensate for the destabilizing effects of the cytostatic on membrane organization. The polar lipids from cells grown in the basal medium containing tamoxifen are also altered, but these alterations do not promote order increase of the bilayer in spite of a deviation of Tm to higher temperatures as detected by DPH. Data indicate that B. stearothermophilus controls the membrane lipid composition in response to tamoxifen, to compensate for TAM-promoted disordering in membranes and to provide an appropriate packing of phospholipid molecules in a stable bilayer, putatively disturbed by TAM incorporation.